Optical path length and wavelength selection using Vis/NIR spectroscopy for olive oil's free acidity determination - Garcia Martin, Juan Francisco (International journal of food science & technology, 2015)
Summary Four different optical path lengths, namely 0.5, 1, 5 and 10 mm, were assayed for olive oil's free acidity determination using Vis/NIR spectroscopy. Results illustrated that the use of higher path length during spectra acquisition resulted in more accurate PLS models, especially when using solely the NIR region. The PLS model obtained with the NIR spectrum using the 10‐mm cuvette was subjected to optimisation by Monte Carlo uninformative variable elimination (MCUVE) and successive projections algorithm (SPA). Both methods drastically reduced the number of spectral variables and markedly improved the performance of the PLS model, especially the SPA‐PLS model, which achieved a SEP (0.051) quite close to SEL (0.048). Interestingly, only twelve of the eighty spectral variables selected by SPA were among the 314 variables provided by MCUVE. All in all, NIRS incorporated to MCUVE‐PLS or SPA‐PLS may be applied as an alternative method for the rapid determination of olive oil's free acidity. Scheme for selecting optical path length and wavelengths in the olive oil's free acidity determination by VisNIR spectroscopy.